Ferrates(FeVI, FeV, and FeIV) oxidation of iodide: Formation of triiodide. (February 2016) - Kralchevska, Radina P.; Sharma, Virender K.; Machala, Libor; Zboril, Radek
Abstract: The presence of iodide (I − ) in water during disinfection and oxidative treatment of water is a potential health concern because of the formation of iodinated disinfection by-products (DBPs), which may be more toxic than chlorinated DBPs. The kinetics of the oxidation of I − by a greener oxidant, ferrate(VI) ( Fe VI O 4 2 −, Fe(VI)) was determined as a function of pH. The second-order rate constants ( k, M −1  s −1 ) decreased from 3.9 × 10 4  M −1  s −1 at pH 5.0 to 1.2 × 10 1  M −1  s −1  at pH 10.3. The kinetics results could be described by the reactivity of monoprotonated species of Fe(VI) ( HFe VI O 4 − ) with I − . In excess I − concentration, triiodide ( I 3 − ) was formed and the stoichiometry of ∼1:1 ([Fe(VI)]:[ I 3 − ]) was found in both acidic and basic pH. Ferrate(V) ( Fe V O 4 3 −, Fe(V)) and ferrate(IV) ( Fe VI O 4 4 −, Fe(IV)) also showed the formation of I 3 − in presence of excess I − . A mechanism of the formation of I 3 − is proposed, which is consistent with the observed stoichiometry of 1:1. The oxidative treatment of I − in water will be rapid ( t 1/2  = 0.6 s at pH 7.0 using 10 mg L −1  K2 FeO4 ). The implications of the results and their comparison with the oxidation of I − by conventional disinfectants/oxidants in water treatment are briefly discussed. Highlights: Rates for oxidation of I − by Fe(VI) decrease with increase in pH. All ferrates form triiodide in reactions with I − in acidic and basic medium. Mechanism describes the rates and stoichiometry of the reactions. Removal of I − by Fe(VI) can be accomplished in seconds.